A Study of the Cultural and Musical Structure of Indian Classic Music for Critical Rereading of the Book “The Music of Northern India” - Navid Vaziri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This paper has attempted to reread the book The Music of Northern India from the collections of the musical experiments as a symbol of culture collection, and the aim of this research is to criticize the mentioned book considering the musical-technical dual discussions and the musical-social issues. Regarding that, this paper mentions the details for discovering the totals, the executive logic behind the paper is comparative, and its aims are analytical, descriptive, and comparative. Analyzing the technical-musical data of the mentioned book is in line with comparing some concepts of Iranian classical music. The role of the non-words and improvising elements in the creation of Indian classical music is the main issue of the criticism. The role of music in the mental life of India, social changes and, of course its influences on Indian music is another issue for discussion in this paper. Considering the text of the book and analyzing the text, we can understand that globalization not only has influenced the social life of the Indian music but also has been influential on musical sound and inter-social relations. It seems that the sound content of the Ragas in Indian music lacks any clear definition, and we face a series of definitions that reading and mental record of the musician, in line with performance atmosphere, have played an important role in the formation of the music. Tala, which is related to the musical timing of Indian music, is like a chain whose rings are formed by the verbal syllables and the art of the melodic instrument players, percussions, and the dancers relate them to each other.